ДОСЛІДЖЕННЯ РЕЗОНАНСНОГО ІНВЕРТОРА ДЛЯ ІНДУКЦІЙНОГО НАГРІВАННЯ З СТАБІЛІЗАЦІЄЮ ПОТУЖНОСТІ НАВАНТАЖЕННЯ - Бєлоха, Г.С.; Морозов, Д.І. (Інститут електродинаміки Національної академії наук України, 2018)
Presents voltage source inverter for induction heating applications, which is characterized by the power control based. The output power control is achieved by varying the shape of the voltage up applied to the resonant circuit. This power control strategy allows the inverter to work to the resonance frequency for all output-power levels. Control of the heating temperature is performed by controlling the resonance inverter power load. The simulation results of are presented. The way of determining the resonant inverter properties by using analytical calculations based on the inverter output voltage distribution on the first harmonic of is presented. Referenses 6, figures 4.